Interaction of Medicinal Plants and Their Active Constituents With Potassium Ion Channels: A Systematic Review - Rajabian, Arezoo; Rajabian, Fatemeh; Babaei, Fatemeh; Mirzababaei, Mohammadreza; Nassiri-Asl, Marjan; Hosseinzadeh, Hossein (Frontiers in Pharmacology, 2022)
Potassium ion (K+) channels are pore-forming transmembrane proteins that control the transport of K+ ions. Medicinal plants are widely used as complementary therapies for several disorders. Studies have shown that the modulation of K+ channels is most likely involved in various pharmacological effects of medicinal plants. This review aimed to evaluate the modulatory effects of medicinal plants and their active constituents on K+ channels under pathological conditions. This systematic review was prepared according to the Preferred Reporting Items for the Systematic Reviews and Meta-analyses (PRISMA) 2020 guideline. Four databases, including PubMed, Web of Science, Embase, and Scopus, were searched. We identified 687 studies from these databases, from which we selected 13 in vivo studies for the review by using the Population, Intervention, Comparison, Outcomes, Study (PICOS) tool. The results of the 13 selected studies showed a modulatory effect of medicinal plants or their active constituents on ATP-sensitive potassium channels (KATP), and small (SKCa) and large (BKCa) conductance calcium-activated K+ channels in several pathological conditions such as nociception, brain ischemia, seizure, diabetes, gastric ulcer, myocardial ischemia-reperfusion, and hypertension via possible involvement of the nitric oxide/cyclic GMP pathway and protein kinase. K+ channels should be considered as significant therapeutic milestones in the treatment of several diseases. We believe that understanding the mechanism behind the interaction of medicinal plants with K+ channels can facilitate drug development for the treatment of various K+ channel-related disorders.